Photovoltaics: Seeing Down to the Bottom: Nondestructive Inspection of All‐Polymer Solar Cells by Kelvin Probe Force Microscopy (Adv. Mater. Interfaces 18/2016). Issue 18 (20th September 2016) - Cui, Zequn; Sun, Jianxia; Landerer, Dominik; Sprau, Christian; Thelen, Richard; Colsmann, Alexander; Hölscher, Hendrik; Ma, Wanli; Chi, Lifeng
Abstract : The material composition in a bulk‐heterojunction of an all‐polymer solar cell is analyzed by Hendrik Hölscher, Wanli Ma, Lifeng Chi, and co‐workers down to the bottom surface by Kelvin probe force microscopy in article 1600446. The phase separation of the composites, both on the top and at the bottom of a BHJ can be measured and reconstructed with this easy‐to‐use approach in a non‐destructive way.